ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKADEMIK DI STMIK AMIKOM PURWOKERTO - Giat Karyono (Universitas Amikom Purwokerto, 2009)
Academic Information Systems is one of the main functions in a data processing activities of students in Higher Education